IoTbased smart irrigation system - Abid, Mohamed nadhir (جامعة الوادي University of Eloued, 2018)
الزراعة كانت دائما عملا شاقا ومستهلكة للوقت, هذه الدراسة هي محاولة لجعلها سهل واقل استهلاكا للوقت , خاصة المناطق الصحراوية حيث تكون الحرارة مرتفعه ومساحات كبيرة وهذه المعايير غير ملائمة للزراعة. وللوصول لهذه الاهداف قمنا بتطبيق مختلف التقنيات مثل الذكاء الاصطناعي و انترنت الاشياء وكذا الحوسبة السحابية, لانشاء نظام ري ذكي . انطلاقا من معلومات مستقبلة من الحساسات التي تستكشف حالة الطقس ورطوبة الارض وكذا شروط الري للنبتة, يحدد النظام الذي يستخدم العامل الذكي ما اذا كان على النظام سقي النبة ام لا. نظامنا هذا يمكن التحكم فيه بطريقة يدوية في الوقت الحقيقي مع امكانية جدولة الوقت. Agriculture has been always hard and tedious job. This study is an effort to makeiteasy and less time consuming especially in deserted areas where heat and large spaces are inconveniencing criteria. To reach these objectives we applied different technologies such as Artificial Intelligence, Internet of Things and Cloud computing to realize smart irrigation system. Based on received information from sensors detecting weather condition, soil moister, and irrigation conditions of the plant, the system using intelligent agent decides whether to irrigate the plants or not. The irrigation system is enabled also with a manual control option that works in real time with time scheduling possibility.
Mémoire Master en informathique
Keywords: ذكاء اصطناعي, انترت الاشياء, الحوسبة السحابية, العامل الذكي, السقي, الزراعة, الوقت الفعلي; Artificial Intelligence, IoT, Cloud Computing, Agent, Irrigation, Real time